2018
DOI: 10.1080/00207144.2018.1494444
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Efficacy of Acupuncture and Hypnotherapy in Patients With Migraine

Abstract: This study investigated the effect of acupuncture, hypnotherapy, and pharmacotherapy in migraine treatments among 90 patients. They were divided into 3 groups of 30 persons each. Group 1, Group 2, and Group 3 were treated with acupuncture, hypnotherapy, and pharmacotherapy, respectively. Changes in the visual analog scale (VAS) and Migraine Disability Assessment (MIDAS) scores from baseline were monitored. Reductions in the percentages of the VAS and MIDAS scores at the end of the third month were significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…For the diagnosis of migraine, three non-Chinese studies adopted internationally recognized diagnostic criteria ( 23 25 ), and the remaining 25 Chinese studies used international or Chinese diagnostic criteria. Chinese diagnostic criteria for migraine without aura are as fellow: A. at least 5 attacks in accordance with B-D characteristics; B. headache attacks (untreated or ineffective) lasting for 4 to 72 h; C. at least 2 headache characteristics as follows 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the diagnosis of migraine, three non-Chinese studies adopted internationally recognized diagnostic criteria ( 23 25 ), and the remaining 25 Chinese studies used international or Chinese diagnostic criteria. Chinese diagnostic criteria for migraine without aura are as fellow: A. at least 5 attacks in accordance with B-D characteristics; B. headache attacks (untreated or ineffective) lasting for 4 to 72 h; C. at least 2 headache characteristics as follows 1.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies ( 29 , 36 – 39 ) used TCD to evaluate changes in intracranial blood flow, among which two were measured after completion of treatment and the other three were measured 1 month after treatment, the TCD examination was performed outside migraine attacks. The degree of pain exhibited by the patients was measured with the VAS in 16 studies ( 19 , 20 , 25 , 26 , 29 , 31 , 33 – 35 , 38 – 44 ). A total of 17 studies ( 18 , 20 , 21 , 23 , 27 – 31 , 34 – 39 , 43 , 45 ) evaluated the treatment efficiency by referring to the following criteria: clinically curative, the pain disappeared after the treatment and no recurrence was observed after follow-up; effective, the degree of pain is reduced and the frequency/duration of attacks lessened; ineffective: no significant reduction or aggravation of symptoms was observed after treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other control interventions (all one study each) included hypnotherapy, 29 bloodletting, 30 flunarizine hydrochloride plus needling at non-acupoints, 31 and Yamamoto new scalp acupuncture. 32 Risk of Bias Figure 3 shows the risk of bias in each of the six domains for all included studies.…”
Section: Control Intervention Characteristicsmentioning
confidence: 99%
“…One trial compared the effect of acupuncture with hypnotherapy and concluded that both treatments were effective in treating migraine headaches. 29 Traditional Acupuncture versus Other Acupuncture Methods…”
Section: Acupuncture Versus Hypnotherapymentioning
confidence: 99%